International Female Graduate Students' Experience at a Midwestern University: Sense of Belonging and Identity Development - Anh T. Le (Journal of International Students, 2016)
International female graduate students have to negotiate multiple aspects of their identities as non-native learners and women in a society with different gender norms than their home countries. However, their experiences have not been well researched within the scholarship on international students. In this study, using the phenomenological approach, we explored the phenomenon of being an international female graduate student in the U.S. The seven participants are diverse in terms of countries of origin, academic programs, and life situations. Using open-ended questions, we conducted indepth one-on-one interviews with the participants. The findings indicate that the participants perceived being international female graduate students at this university as a positive, life-changing, and transformative experience.